How can we Minimise Pain During and After Carpal Tunnel Decompression? - Muhammad Waseem Anwar, Mudassar Nazar, Abul Qayum Baig, Shabbir Ahmad, Muhammad Imran, Rashid Usman, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Our Study objective was to asses pain severity in a series of patients who underwent carpal tunnel release (CTR) surgery with a technique that minimise tourniquet inflation time. Material and Method: Our study represented a prospective case series conducted from June 2021 to Dec 2021 in Islam Medical College Sialkot and CMH Lahore. A total of 160 patients with a clinical diagnosis and positive EMG/NCS were included. The patients were asked to complete a proforma which assesses pain on basis of Visual Analogue Scale (VAS) at 3 occasions; (1) at initial out patient appointment (2) in post operative area after surgery (3) at 12 weeks post CTR surgery. Questions were asked to assess pain severity at surgery site and over area of tourniquet inflation. Results: 160 patients were included in our study with a median age of 50years (range 33-65). There were 110 females and 50 males (ratio 2.2:1). The average tourniquet time was 8 minutes (range 6-9.5). 91.8% (n-147) of our patients had a VAS of 1 at both the wound and tourniquet site post-operatively. 5% had a score of 3 and 4.2 had a VAS score of 4 (n-8 and n-5 respectively). 27 were operated in past for contralateral CTD as well and remaining 133 patients said they would prefer to be operated for other side by similar method. Conclusion: Our technique is safe and effective in reducing pain post CTR surgery.